Presence of toxoplasma gondii tissue cysts in human semen: toxoplasmosis as a potential sexually transmissible infection - Tong, Wen Han (2023)
Toxoplasma gondii is a widely prevalent protozoan parasite in human populations. This parasite is thought to be primarily transmitted through undercooked meat and contamination by cat feces. Here, we seek to determine if Toxoplasma gondii cysts can be found within human semen.